From Toxins Targeting Ligand Gated Ion Channels to Therapeutic Molecules - Nasiripourdori, Adak (MDPI, 2011)
Ligand-gated ion channels (LGIC) play a central role in inter-cellular communication. This key function has two consequences: (i) these receptor channels are major targets for drug discovery because of their potential involvement in numerous human brain diseases; (ii) they are often found to be the target of plant and animal toxins. Together this makes toxin/receptor interactions important to drug discovery projects. Therefore, toxins acting on LGIC are presented and their current/potential therapeutic uses highlighted.